The Effect of Early Maternal Separation Combined With Adolescent Chronic Unpredictable Mild Stress on Behavior and Synaptic Plasticity in Adult Female Rats - Huang, Jiawen; Shen, Chongkun; Ye, Ran; Shi, Yafei; Li, Weirong (Frontiers in Psychiatry, 2021)
Our aims were to evaluate the depression model of early maternal separation (MS) combined with adolescence chronic unpredictable mild stress (CUMS) in female adult SD rats, to observe the behavior and the expressions of synaptic proteins in rats, and to provide a reference for screening of antidepressant drug activity. In our study, MS and CUMS were conducted to establish a dual stress model on female rats. Behavioral tests, including sucrose preference test, open field test, zero maze test, were used to detect depression-like and anxiety-like behavior of animals. Nissl staining was used to detect the number of neuronal cells in the hippocampus CA1 and DG regions of rats from each group. Synaptophysin (SYN), postsynaptic density-95 (PSD-95) and growth-associated protein-43 (GAP-43) expressions in hippocampus were detected by western blot. Expression of hippocampus SYN protein was further detected by immunohistochemistry. Rats in MS+CUMS group presented more serious depression-like and anxiety-like behavior than in MS group. Also, few Nissl bodies in the hippocampus CA1 and DG regions, less percentage of SYN-positive cells and down-regulated expressions of SYN, PSD-95 and GAP43 were found in hippocampus of rats in MS+CUMS group. In conclusion, adult female rats that had undergone MS and CUMS performed more critical depression-like and anxiety-like behaviors, and this process may be resulted from synaptic plasticity impairing.